ISLAMIC CINVENTION CENTER NAHDHATUL KAHAIRAAT DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR - Talibe, Mohamad Anwar; Tamrin, Moh. Muhrim; antu, Evi Sunarti (Venustas, 2022)
Besides Al-Khairaat Foundation playing a role in the field of education, it also takes a part in the field of da'wah and community development. Da'wah is not merely the appearance of a preacher by merely expressing religious values in society. It also contains a broad understanding covering all aspects of life, especially in the Sangtombolang subdistrict. The Islamic Convention Center of Nahdhatul Khairaat provides an identity for Cempaka village, Sangtombolang subdistrict. It is the reason for the planning of the building "Islamic Convention Center of Nahdhatul Khairaat with a Neo-Vernacular Architectural Approach" with the overall goal of being a place or place for all conventional Nahdhatul Khairaat activities. Keywords: Traditional, Culinary Tourism, Neo Vernacular Architecture Yayasan Al-Khairaat juga Selain bidang pendidikan, mengambil peran di bidang dakwah dan pengembangan kemasyarakatan. Dakwah bukan semata-mata tampilan dai‟ yang sekedar mengungkapkan masalah agama di tengah-tengah masyarakat, akan tetapi mangandung pengertian yang luas yang mencakup semua aspek kehidupan khususnya di Kecamatan Sangtombolang. Islamic Convention Center Nahdhatul Khairaat memberikan identitas bagi desa Cempaka Kecamatan Sangtombolang, maka perencanaan gedung “Islamic Convention Centre Nahdhatul Khairaat dengan Pendekatan Arsitektur Neo-Vernakular”, dengan tujuan secara keseluruhan adalah suatu wadah atau tempat pemusatan segala kegiatan Nahdhatul Khairaat yang bersifat konvensional. Kata kunci : Nahdhatul Khairaat, Islamic Convension Center, Neo Vernakular